An All‐Solid‐State Battery Based on Sulfide and PEO Composite Electrolyte. Issue 29 (23rd June 2022) - Su, Yong; Zhang, Xuedong; Du, Congcong; Luo, Yang; Chen, Jingzhao; Yan, Jitong; Zhu, Dingding; Geng, Lin; Liu, Shuangxu; Zhao, Jun; Li, Yanshuai; Rong, Zhaoyu; et al.
Abstract: Replacing liquid electrolytes with solid polymer electrolytes (SPEs) is considered as a vital approach to developing sulfur (S)‐based cathodes. However, the polysulfides shuttle and the growth of lithium (Li) dendrites are still the major challenges in polyethylene oxide (PEO)‐based electrolyte. Here, an all‐solid‐state Li metal battery with flexible PEO‐Li10 Si0.3 PS6.7 Cl1.8 (LSPSCl)‐C‐lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) composite cathode (FCC) and PEO‐LSPSCl‐LiTFSI composite electrolyte (S‐CPE) is designed. The initial capacity of the Li|S‐CPE|FCC battery is 414 mAh g −1 with 97.8% capacity retention after 100 cycles at 0.1 A g −1 . Moreover, the battery displays remarkable capacity retention of 80% after 500 cycles at 0.4 A g −1 . Cryo‐transmission electron microscopy (Cryo‐TEM) reveals rich large‐sized Li2 CO3 particles at the Li/PEO interface blocking the Li + transport, but the layer with rich Li2 O nanocrystals, amorphous LiF and Li2 S at the Li/S‐CPE interface suppresses the growth of lithium dendrite and stabilizes the interface. In situ optical microscopy demonstrates that the excellent cyclic stability of FCC is ascribed to the reversible shuttle of P–S–P species, resulting from the movement of ether backbone in PEO. This study provides strategies to mitigate the polysulfide shuttle effect and Li dendrite formation in designing high energy density solid‐state Li–S‐based batteries. Abstract : A flexible all‐solid‐state Li metal battery with PEO‐Li10 Si0.3 PS6.7 Cl1.8 (LSPSCl)‐C composite cathode (FCC) and PEO‐LSPSCl composite electrolyte (S‐CPE) is designed. The excellent cyclic stability of flexible battery is ascribed to reversible shuttle of P–S–P species and suppressed Li dendrite.